2015
DOI: 10.1017/iop.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness at Work: A New Approach to Improving Individual and Organizational Performance

Abstract: In recent years the concept of mindfulness has become increasingly popular, and with good reason. A growing body of research indicates that mindfulness provides a number of physical, psychological, and even performance benefits. As a result, some organizations have started offering mindfulness programs to their employees. But despite growing interest, mindfulness has received little attention from the industrial–organizational community. In this article, we provide an overview of what mindfulness is, where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
225
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(238 citation statements)
references
References 88 publications
5
225
1
7
Order By: Relevance
“…
I am happy to see the topic of mindfulness at work find its way into this journal as a focal article (Hyland, Lee, & Mills, 2015), and I read it with great interest. Although I agree with most of the points made, I want to elaborate on some critical issues that were not or were only briefly touched on and that I deem worthy of further exploration and discussion.

With the current surge in popularity of mindfulness trainings in organizations, it is our responsibility as (mindfulness) researchers to ensure that mindfulness interventions are used for the right goals and implemented so that they benefit the participating individuals.

…”
mentioning
confidence: 99%
“…
I am happy to see the topic of mindfulness at work find its way into this journal as a focal article (Hyland, Lee, & Mills, 2015), and I read it with great interest. Although I agree with most of the points made, I want to elaborate on some critical issues that were not or were only briefly touched on and that I deem worthy of further exploration and discussion.

With the current surge in popularity of mindfulness trainings in organizations, it is our responsibility as (mindfulness) researchers to ensure that mindfulness interventions are used for the right goals and implemented so that they benefit the participating individuals.

…”
mentioning
confidence: 99%
“…Baruch College and The Graduate Center, The City University of New York As pointed out by Hyland, Lee, and Mills (2015), the most prominent effect of mindfulness is a significant decrease in experienced stress levels, and one of the most popular mindfulness interventions is mindfulness-based stress reduction. When it comes to psychological stress, desirable outcomes are both expected and documented for employees who adopt a mindful approach to work.…”
Section: How Does Employee Mindfulness Reduce Psychological Distress?mentioning
confidence: 99%
“…In a review of mindfulness interventions,3 it was found that the majority of researchers (~60%) used pre–post self-report mindfulness measures, such as Mindful Attention Awareness Scale (MAAS) 4. In constructing the MAAS, Brown and Ryan assert that the MAAS scale measures ‘a disposition … focused on the presence or absence of attention to and awareness of what is occurring in the present’ (Brown, p. 824) 4…”
Section: Introductionmentioning
confidence: 99%